A Self‐Powered Dynamic Displacement Monitoring System Based on Triboelectric Accelerometer. Issue 19 (8th June 2017) - Yu, Hua; He, Xu; Ding, Wenbo; Hu, Yongshan; Yang, Dongchen; Lu, Shan; Wu, Changsheng; Zou, Haiyang; Liu, Ruiyuan; Lu, Canhui; Wang, Zhong Lin
Abstract: An integrated self‐powered dynamic displacement monitoring system by utilizing a novel triboelectric accelerometer for structural health monitoring is proposed and implemented in this study, which can show the dynamic displacement and transmit the alarming signal by accurately sensing the vibration acceleration. The fabricated triboelectric accelerometer based on the noncontact freestanding triboelectric nanogenerator consists of an outer transparent sleeve tube and an inner cylindrical inertial mass that is suspended by a highly stretchable silicone fiber. One pair of copper film electrodes is deposited by physical vapor deposition on nylon film and adhered on the inner wall of the outer tube, while a fluorinated ethylene propylene film with nanowire structures is adhered on the surface of the inner cylindrical inertial mass. The experimental results show that proposed triboelectric accelerometer can accurately sense the vibration acceleration with a high sensitivity of 0.391 V s 2 m −1 . In particular, the developed accelerometer has superior performance within the low‐frequency range. One of the most striking features is that the commercial accelerometer using piezoelectric material is strongly dominated by high‐order harmonics, which can cause confusion in computer data analysis. In contrast, the triboelectric accelerometer is only dominated by the base resonance mode. Abstract : Based on the noncontact freestanding triboelectric nanogenerator (TENG), a novel self‐powered accelerometer sensor with the sleeve‐tube structure for vibration detection is proposed and fabricated, which has more superior performance applying in lower vibration frequency compared with the traditional piezoelectric accelerometer. Moreover, an integrated self‐powered dynamic displacement monitoring system by utilizing a novel triboelectric accelerometer for structural health monitoring is developed.